Aplikasi Game Edukasi Pengenalan Kosakata Bahasa Inggris Berbasis Mobile - Fernando Irawan; Justinus Andjarwirawan; Yulia Yulia (Jurnal Infra, 2016)
English is universal language that important and have big impact in the world of work and social work. But the children prefer playing than learning something new like English. One game that is loved by children are playing smartphone because children are now begin to have access to a smartphone.Therefore, in order to make children can learn English in an activity favored by them. Educational game made for the introduction of the English vocabulary-based Mobile. One of the methods used by teachers in teaching is the Total Physical Response associated with body movements.Thust the system utilize the use of accelerometer sensors that record the movement on smartphones to increase interest in children's learning.Overall this system can help children to gain knowledge about the English vocabulary so hopefully with this application, children can be more interested in mastering the English language so that it can be a start for success in the future.